2020
DOI: 10.1016/j.envpol.2020.115327
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity the missing link between COVID-19 severity and air pollution?

Abstract: In the previous publication “Can atmospheric pollution be considered a co-factor in extremely high level of SARS-CoV-2 lethality in Northern Italy?” Conticini et al. hypothesized that the surplus of lethality of the novel SARS-CoV-2 in Northern Italy may be at least in part explained by the evidence of highest pollution reported in this area, as both severe COVID-19 and smog exposure are correlated to an innate immune system hyper-activation with subsequent lung inflammation and injury. Since this hypothesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…In Phase I ( Phase II ), an increase in 1 metric ton in PM2.5 (log) per year would increase the COVID-19 death rate by a factor of 1.25 ( 1.96 ). The finding agrees with relevant studies tackling the atmospheric determinants of population’s vulnerability to COVID-19 in the U.S. ( Bashir et al, 2020 ; Wu et al, 2020 ), Italy ( Lubrano et al, 2020 ), China ( Lin et al, 2020a ), and some Latin American cities ( Bolaño et al, 2020 ). All of them unanimously confirmed the correlation between atmospheric conditions and COVID-19 cases, making poor air quality an additional co-determinant of COVID-19 lethality.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In Phase I ( Phase II ), an increase in 1 metric ton in PM2.5 (log) per year would increase the COVID-19 death rate by a factor of 1.25 ( 1.96 ). The finding agrees with relevant studies tackling the atmospheric determinants of population’s vulnerability to COVID-19 in the U.S. ( Bashir et al, 2020 ; Wu et al, 2020 ), Italy ( Lubrano et al, 2020 ), China ( Lin et al, 2020a ), and some Latin American cities ( Bolaño et al, 2020 ). All of them unanimously confirmed the correlation between atmospheric conditions and COVID-19 cases, making poor air quality an additional co-determinant of COVID-19 lethality.…”
Section: Resultssupporting
confidence: 90%
“…In the context of Mexico, our results at the municipal-level indicate that, regardless of lockdown policies, metabolic disorders, such as obesity or diabetes, can exacerbate infections and deaths. Our findings agree with the findings of Lubrano et al (2020) , who demonstrated that the extremely high level of COVID-19 lethality in Northern Italy, compared to the rest of the country, can be explained by differences in air pollution and obesity. Sanchis-Gomar et al (2020) also supported the above-mentioned link between obesity/air pollution and higher COVID-19 lethality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, an enormous amount of scientific literature has provided strong evidence that climate factors such as high air temperature or exposure to air pollution lead to an increase of lethality rates (Lin et al, 2020a,b; Ahmadi et al, 2020; Bashir et al, 2020; Riccò et al, 2020; Sobral et al, 2020). This has been explained by the contribution of air pollution to respiratory tract infections, pulmonary disease, or diabetes burden (Lubrano et al, 2020; Ma et al, 2020; Xu et al, 2020). Mexico, with vastly different climates among its states and municipalities, has presented differentiated effects on COVID-19 confirmed cases (Méndez-Arriaga, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 ), climatic (i.e. temperature and humidity), and socio-economic inequality – all of these factors are widely documented [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. Understandably, most of the confirmed cases are based on test results against symptomatic cases and asymptomatic cases are generally undocumented.…”
Section: Introductionmentioning
confidence: 99%